Cathode composite material, cathode pole piece, preparation methods of cathode composite material and cathode pole piece, and battery and electric equipment comprising cathode pole piece

By covering the solid electrolyte on the surface of the cathode material, the problem of side reactions during the cycle of the secondary battery is solved, and the circulation performance and energy density of the battery are improved.

CN119208549AActive Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310769681.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

There are side reaction problems during the cycle of secondary batteries, which affect the electrochemical performance.

Method used

A cathode composite material, including a cathode material and a solid electrolyte coated on the surface of the cathode material, is arranged in the coating by adjusting the particle size and thickness of the solid electrolyte to reduce contact between the cathode material and the electrolyte and reduce side reactions.

Benefits of technology

Improves the cycling performance of the battery, reduces the storage gas production, and improves the energy density and ion transmission performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208549A_ABST
    Figure CN119208549A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a cathode composite material, a cathode pole piece, respective preparation methods of the cathode composite material and the cathode pole piece, and a battery and electric equipment comprising the cathode pole piece. And the cathode composite material comprises a cathode material and a solid electrolyte coated on the surface of the cathode material. The surface of the cathode material is coated with the solid electrolyte, and under the condition that the cathode composite material is arranged on the coating, the contact between the cathode material and the electrolyte is reduced, the side reaction is reduced, and the battery performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a cathode composite material, a cathode pole piece and respective preparation methods, as well as a battery and an electrical device comprising the cathode pole piece. Background Art

[0002] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.

[0003] There are problems with side reactions during the cycle of secondary batteries. Summary of the invention

[0004] The main purpose of this application is to provide a cathode composite material to improve the performance of the battery.

[0005] To achieve the above-mentioned purpose, the present application proposes a cathode composite material, which includes a cathode material and a solid electrolyte coated on the surface of the cathode material.

[0006] The surface of the cathode material is coated with a solid electrolyte. When the cathode composite material is arranged on a coating, it helps to reduce the contact between the cathode material and the electrolyte, reduce side reactions, and improve battery performance.

[0007] Optionally, the ratio of the volume average particle size Dv50 of the solid electrolyte to the volume average particle size Dv50 of the cathode material is 1:400 to 1:10, preferably, 1:300 to 1:50.

[0008] In order to improve the problem that the solid electrolyte has a large particle size and is difficult to coat on the surface of the cathode material, the ratio of the volume average particle size Dv50 of the solid electrolyte to the volume average particle size Dv50 of the cathode material is 1:400 to 1:10, preferably, 1:300 to 1:50.

[0009] Optionally, the volume average particle size Dv50 of the solid electrolyte ranges from 1 nm to 1000 nm, preferably from 10 nm to 500 nm;

[0010] And / or, the volume average particle size Dv50 of the cathode material is in the range of 100 nm to 20000 nm, preferably, 500 nm to 5000 nm.

[0011] In order to improve the coating of the solid electrolyte on the surface of the cathode material, the volume average particle size Dv50 of the solid electrolyte ranges from 1 nm to 1000 nm, preferably, from 10 nm to 500 nm.

[0012] In order to improve the coating of the solid electrolyte on the surface of the cathode material and improve the risk of contact between the cathode material and the electrolyte, the volume average particle size Dv50 of the cathode material ranges from 100nm to 20000nm, preferably, from 500nm to 5000nm.

[0013] Optionally, the solid electrolyte is spaced apart on the surface of the cathode material;

[0014] And / or, the thickness of the solid electrolyte is in the range of greater than 0 and less than or equal to 3 μm, preferably, greater than 0 and less than or equal to 100 nm.

[0015] The present application does not limit the coating method of the solid electrolyte on the surface of the cathode material. Considering that the transmission of lithium ions in the cathode material (taking lithium-ion batteries as an example, of course it can also be other types of secondary batteries) is mainly achieved by the electrolyte, although the solid electrolyte can also achieve the transmission of lithium ions, its transmission capacity is not as good as the electrolyte. In order to improve the barrier of the solid electrolyte layer to the electrolyte and affect the transmission of lithium ions by the electrolyte, the solid electrolyte is spaced on the surface of the cathode material. In this way, it is convenient to leave gaps on the surface of the cathode material, which helps the electrolyte to contact the cathode material and improve the transmission of lithium ions.

[0016] In order to improve the problem of impedance increase caused by coating of the solid electrolyte on the surface of the cathode material, the thickness of the solid electrolyte ranges from greater than 0 to less than or equal to 3 μm, preferably, greater than 0 to less than or equal to 100 nm.

[0017] Optionally, the ratio of the mass of the solid electrolyte to the mass of the cathode material is 1:200 to 1:50, preferably, 1:150 to 1:60.

[0018] In order to improve the problem of side reactions caused by direct contact between the electrolyte and the cathode material, and to improve the problem of reducing the battery energy density due to the addition of solid electrolyte, the ratio of the mass of the solid electrolyte to the mass of the cathode material is 1:200 to 1:50, preferably, 1:150 to 1:60.

[0019] Optionally, the solid electrolyte includes at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0020] The present application does not limit the type of solid electrolyte, including but not limited to at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0021] Optionally, the polymer solid electrolyte includes at least one of polyethylene oxide, polymethacrylate, and polyvinylidene fluoride;

[0022] And / or, the oxide solid electrolyte includes Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4、Li7La3Zr2O 12 , LiPON(Li2PO2O);

[0023] And / or, the sulfide solid electrolyte Li2S-P2S5, Li2S-P2S5-MS x At least one of, M includes at least one of Si, Sn, Al, Se, and Ge.

[0024] The polymer solid electrolyte includes but is not limited to at least one of polyethylene oxide, polymethacrylate, and polyvinylidene fluoride.

[0025] Oxide solid electrolytes include but are not limited to Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4、Li7La3Zr2O 12 , LiPON(Li2PO2O).

[0026] Sulfide solid electrolytes include but are not limited to Li2S-P2S5, Li2S-P2S5-MS x At least one of, M includes at least one of Si, Sn, Al, Se, and Ge.

[0027] The present application also provides a cathode electrode plate, which includes a current collector and a coating disposed on at least one side of the current collector, wherein the coating includes the cathode composite material as described above.

[0028] The coating includes a cathode composite material, which includes a cathode material and a solid electrolyte coated on the surface of the cathode material. The solid electrolyte is used for ion transmission, improves the direct contact between the cathode material and the electrolyte, improves the problem of intercrystalline cracks / intracrystalline cracks in the cathode material, and is beneficial to reduce side reactions, improve battery cycle performance, and reduce the storage gas production of the battery.

[0029] Optionally, the mass percentage of the cathode composite material to the total mass of the coating is in the range of 80% to 98%, preferably, 85% to 95%.

[0030] In order to improve the performance of the battery, the mass percentage of the cathode composite material to the total mass of the coating layer is in the range of 80% to 98%, preferably, 85% to 95%.

[0031] It can be understood that the coating is a one-layer structure, which may include a cathode composite material. The coating may also be a multi-layer structure, in which at least one layer includes a cathode composite material, and at least another layer may not include a cathode composite material. For example, the coating includes a two-layer structure, the first layer is arranged close to the current collector, and the second layer is arranged on the surface of the first layer. In this case, the first layer may include a cathode composite material, and the second layer may include a cathode material.

[0032] Optionally, the mass percentage of the solid electrolyte in the cathode composite material to the total mass of the coating layer is in a range of 0.4% to 2%.

[0033] In order to improve the performance of the battery, the mass percentage of the solid electrolyte in the cathode composite material to the total mass of the coating is in the range of 0.4% to 2%. It can be understood that as the concentration of the solid electrolyte in the cathode composite material in the coating increases, the probability of the cathode material and the electrolyte having a side reaction decreases, but as the concentration of the solid electrolyte in the cathode composite material in the coating continues to increase, the pole piece impedance increases and the gram capacity decreases.

[0034] Optionally, the coating layer comprises at least two active layers, the at least two active layers are stacked and arranged on the same side of the current collector, at least one of the active layers is arranged on the current collector, and at least another of the active layers is arranged on a side of at least one of the active layers away from the current collector;

[0035] The mass percentage of the solid electrolyte in at least one of the active layers is defined as W1, and the mass percentage of the solid electrolyte in at least another active layer is defined as W2, satisfying W1>W2.

[0036] One active layer is arranged on the current collector, and the other active layer is arranged on the side of the active layer away from the current collector. Thus, according to the distance from the current collector, one active layer is arranged close to the current collector, and the other active layer is arranged far away from the current collector. The mass percentage W1 of the solid electrolyte in the active layer close to the current collector is greater than the mass percentage W2 of the solid electrolyte in the active layer far away from the current collector. In this way, the contact between the electrolyte and the cathode material in the active layer close to the current collector is reduced, the infiltration of the electrolyte into the active layer far away from the current collector is improved, the ion transmission performance is improved, and the battery performance is improved.

[0037] It is understandable that, in theory, the transport of ions mainly depends on the electrolyte. Although solid electrolytes have the function of transporting ions, the effect is not as good as that of electrolytes. In order to balance the contact between the electrolyte and the cathode material, solid electrolytes of different concentrations are distributed in different active layers. Specifically, the concentration of the solid electrolyte distributed from close to the current collector to away from the current collector shows a decreasing trend, which improves the side reaction of the cathode material in the active layer close to the current collector, while also maintaining the wetting of the active layer away from the current collector with the electrolyte. While reducing the side reactions caused by the contact between the electrolyte and the cathode material, it also improves the ion transport performance.

[0038] Optionally, 0.4%≤W1≤4%, preferably, 0.4%≤W1≤3%;

[0039] And / or, 0≤W2≤3.5%, preferably 0≤W2≤2.5%.

[0040] In order to improve the contact between the electrolyte and the cathode material, and to improve the ion transport performance, the mass percentage W1 of the solid electrolyte in the active layer close to the current collector satisfies 0.4%≤W1≤4%, preferably 0.4%≤W1≤3%; the mass percentage W2 of the solid electrolyte in the active layer far from the current collector satisfies 0≤W2≤3.5%, preferably 0≤W2≤2.5%.

[0041] Optionally, the compaction density of the coating is in the range of 2.0 g / cm 3 Up to 5.0g / cm 3 , preferably, 2.3 g / cm 3 Up to 4.5g / cm 3 .

[0042] In order to improve the wetting of the electrolyte to the coating and improve the transmission of ions, the compaction density of the coating is in the range of 2.0g / cm 3 Up to 5.0g / cm 3 , preferably, 2.3 g / cm 3 Up to 4.5g / cm 3 .

[0043] Optionally, the coating layer comprises at least two active layers, the at least two active layers are stacked and arranged on the same side of the current collector, at least one of the active layers is arranged on the current collector, and at least another of the active layers is arranged on a side of at least one of the active layers away from the current collector;

[0044] The compaction density of at least one of the active layers is defined as ρ1, and the compaction density of at least another active layer is defined as ρ2, satisfying ρ1>ρ2.

[0045] The compaction density of the coating will increase with the increase of solid electrolyte. As the compaction density increases, the voids in the coating will decrease. In order to balance the side reactions caused by the contact between the cathode material and the electrolyte and to improve the transport of ions, the coating includes at least two active layers. The concentration of the solid electrolyte in the active layer close to the current collector is higher than the concentration of the solid electrolyte in the active layer far away from the current collector. Thus, the compaction density ρ1 of the active layer close to the current collector is greater than the compaction density ρ2 of the active layer far away from the current collector. In this way, the side reactions between the cathode material and the electrolyte in the active layer close to the current collector are improved, the wetting of the active layer far away from the current collector with the electrolyte is improved, and the transport of ions is improved.

[0046] The present application also provides a method for preparing a cathode composite material, comprising:

[0047] A cathode material and a solid electrolyte are prepared, and the cathode material and the solid electrolyte are mixed to obtain a cathode composite material.

[0048] The solid electrolyte is arranged on the surface of the cathode material by simple physical mixing to obtain a cathode composite material. The preparation method is simple, low-cost and convenient for large-scale production.

[0049] Optionally, the step of mixing the cathode material and the solid electrolyte comprises:

[0050] The cathode material and the solid electrolyte are stirred and mixed at a stirring rate of 800 rpm to 2000 rpm and a stirring time of 2 h to 8 h to obtain a cathode composite material.

[0051] In order to mix effectively, the cathode material and the solid electrolyte are stirred and mixed at a stirring rate of 800 rpm to 2000 rpm and a stirring time of 2 h to 8 h to obtain a cathode composite material.

[0052] The present application also provides a method for preparing a cathode electrode sheet, comprising:

[0053] mixing the cathode material with the solid electrolyte to obtain a cathode composite material;

[0054] Mixing the cathode composite material, a binder, a conductive agent and a solvent to obtain a slurry;

[0055] The slurry is coated on a current collector, dried, and cold-pressed to obtain a cathode electrode sheet.

[0056] The cathode material is mixed with a solid electrolyte to obtain a cathode composite material, the cathode composite material, a binder, a conductive agent and a solvent are mixed to obtain a slurry, and the slurry is coated on a current collector, dried and cold pressed to obtain a cathode electrode sheet. This step is simple and convenient for large-scale production.

[0057] Optionally, the step of coating the slurry on a current collector, drying, and cold pressing to obtain a cathode electrode sheet includes:

[0058] Prepare at least two layers of active layer slurry, apply one of the active layer slurry on the current collector, and dry;

[0059] The slurry of the other active layer is coated on the one active layer, dried, and cold pressed to obtain a cathode electrode sheet;

[0060] The mass percentage of the solid electrolyte in the slurry of one active layer is greater than the mass percentage of the solid electrolyte in the slurry of another active layer.

[0061] In order to prepare a multi-layer structure coating, the step of coating the slurry on the current collector, drying, and cold pressing to obtain a cathode electrode sheet includes: preparing slurry of at least two active layers, coating the slurry of one active layer on the current collector, and drying; coating the slurry of another active layer on the active layer, drying, and cold pressing to obtain a cathode electrode sheet; the mass percentage of the solid electrolyte in the slurry of one active layer is greater than the mass percentage of the solid electrolyte in the slurry of another active layer. In this way, the side reaction between the cathode material and the electrolyte in one active layer is improved, the transmission of ions in the other active layer is improved, and the battery performance is improved.

[0062] The present application provides a battery, comprising: an anode electrode piece, a cathode electrode piece, a separator and an electrolyte, wherein the cathode electrode piece is the cathode electrode piece as described above or a cathode electrode piece obtained by the cathode electrode piece preparation method as described above.

[0063] The present application provides an electrical device, wherein the electrical device comprises the above-mentioned battery.

[0064] The cathode composite material of the present application includes a cathode material and a solid electrolyte coated on the surface of the cathode material. The solid electrolyte coated on the surface of the cathode material helps to reduce the contact between the cathode material and the electrolyte, reduce side reactions, and improve battery performance when the cathode composite material is disposed on the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0066] Figure 1 A schematic diagram of the process of preparing the cathode electrode sheet of the present application;

[0067] Figure 2This is a schematic structural diagram of an embodiment of a cathode electrode of the present application;

[0068] Figure 3 This is a schematic structural diagram of an embodiment of a cathode electrode of the present application;

[0069] Figure 4 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0070] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0071] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application;

[0072] Figure 7 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0073] Figure 8 yes Figure 7 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0074] Fig. 9 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0075] Description of Figure Numbers:

[0076] Label name Label name 100 Cathode Piece 3 Lower box 10 current collector 4 Battery Module 20 An active layer 5 Secondary battery 30 Another active layer 51 case 1 Battery Pack 52 Electrode assembly 2 Upper box 53 Top cover assembly

[0077] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0078] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0079] Hereinafter, the cathode composite material, cathode pole piece and respective preparation methods, as well as the battery and electrical equipment containing the cathode pole piece of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0080] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0081] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0082] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0083] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0084] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0085] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0086] Cathode materials can undergo side reactions during secondary battery cycling.

[0087] For example, the cathode material undergoes side reactions when in contact with the electrolyte.

[0088] In order to improve the above problems, the present application provides a cathode composite material, which includes a cathode material and a solid electrolyte coated on the surface of the cathode material.

[0089] Solid electrolyte, a solid substance with ionic conductivity.

[0090] Coating refers to that solid electrolyte particles are arranged on the surface of cathode particles to form a coating state.

[0091] The solid electrolyte coated on the surface of the cathode particles makes the cathode composite material form a core-shell structure. In the core-shell structure, the cathode particles are the core layer, the solid electrolyte is located on the outer surface of the core layer, and the structure coated on the surface of the core layer structure is the shell structure.

[0092] The core-shell structure can be observed through a transmission electron microscope. Specifically, due to the different materials of the core-shell structure, there will be a difference in brightness (mass thickness contrast) between the core layer structure and the shell layer structure in the transmission electron microscope image. The mass thickness contrast is the difference in contrast caused by the differences in thickness and mass in different areas of the sample surface. Since different parts of the sample have different electron scattering abilities, the number of transmitted electrons passing through the objective lens is also different, and thus the electron beam intensity will be different. The image of the area with strong scattering and less transmitted electrons will be dark, and vice versa.

[0093] The surface of the cathode material is coated with a solid electrolyte. When the cathode composite material is arranged on a coating, it helps to reduce the direct contact between the cathode material and the electrolyte, reduce side reactions, and improve battery performance.

[0094] In one embodiment, the ratio of the mass of the solid electrolyte to the mass of the cathode material is 1:200 to 1:50, preferably, 1:150 to 1:60.

[0095] In order to improve the problem of side reactions caused by direct contact between the electrolyte and the cathode material, and to improve the problem of reducing the battery energy density due to the addition of solid electrolyte, the ratio of the mass of the solid electrolyte to the mass of the cathode material is 1:200 to 1:50, preferably, 1:150 to 1:60.

[0096] In the above 1:200 to 1:50, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1:200, 1:190, 1:150, 1:120, 1:100, 1:80, 1:70, 1:50, etc., as well as the range values ​​between any two of the above point values.

[0097] In the above 1:150 to 1:60, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1:150, 1:130, 1:110, 1:100, 1:90, 1:60, etc., as well as the range values ​​between any two of the above point values.

[0098] In one embodiment, the ratio of the volume average particle size Dv50 of the solid electrolyte to the volume average particle size Dv50 of the cathode material is 1:400 to 1:10, preferably, 1:300 to 1:50.

[0099] Dv50 is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. Dv50 is also called the median diameter or median particle size. Dv50 is often used to indicate the average particle size of powders.

[0100] The volume particle size distribution Dv50 can be tested by a method known in the art. For example, GB / T 19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.

[0101] In order to improve the problem that the solid electrolyte has a large particle size and is difficult to coat on the surface of the cathode material, the ratio of the volume average particle size Dv50 of the solid electrolyte to the volume average particle size Dv50 of the cathode material is 1:400 to 1:10, preferably, 1:300 to 1:50.

[0102] In the above 1:400 to 1:10, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1:400, 1:380, 1:350, 1:320, 1:300, 1:280, 1:250, 1:220, 1:200, 1:180, 1:150, 1:120, 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, etc., as well as the range values ​​between any two of the above point values.

[0103] In one embodiment, the volume average particle size Dv50 of the solid electrolyte ranges from 1 nm to 1000 nm, preferably, from 10 nm to 500 nm; and / or, the volume average particle size Dv50 of the cathode material ranges from 100 nm to 20000 nm, preferably, from 500 nm to 5000 nm.

[0104] In order to improve the coating of the solid electrolyte on the surface of the cathode material, the volume average particle size Dv50 of the solid electrolyte ranges from 1nm to 1000nm, preferably, 10nm to 500nm. In order to improve the coating of the solid electrolyte on the surface of the cathode material and to improve the risk of contact between the cathode material and the electrolyte, the volume average particle size Dv50 of the cathode material ranges from 100nm to 20000nm, preferably, 500nm to 5000nm.

[0105] In the above-mentioned 1nm to 1000nm, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1nm, 10nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, etc., and the range value between any two of the above-mentioned point values.

[0106] In the above 100nm to 20000nm, the values ​​include the minimum and maximum values ​​of the range, and each value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 1000nm, 000nm, 1100nm, 1300nm, 1500nm, 1800nm, 2000nm, 2500nm, 3000nm, 3500nm, 4000nm, 4500nm, 5000nm, 5500nm, 6000nm, 6500nm, 7000nm, 7500nm, 8000nm, 8500nm, 9000nm, 10000nm, 15000nm, 20000nm, etc., and the range value between any two of the above point values.

[0107] In one embodiment, the solid electrolyte is spaced apart on the surface of the cathode material;

[0108] And / or, the thickness of the solid electrolyte is in the range of greater than 0 and less than or equal to 3 μm, preferably, greater than 0 and less than or equal to 100 nm.

[0109] The present application does not limit the coating method of the solid electrolyte on the surface of the cathode material. Considering that the transmission of lithium ions in the cathode material (taking lithium-ion batteries as an example, of course it can also be other types of secondary batteries) is mainly achieved by the electrolyte, although the solid electrolyte can also achieve the transmission of lithium ions, its transmission capacity is not as good as the electrolyte. In order to improve the barrier of the solid electrolyte layer to the electrolyte and affect the transmission of lithium ions by the electrolyte, the solid electrolyte is spaced on the surface of the cathode material. In this way, it is convenient to leave gaps on the surface of the cathode material, which helps the electrolyte to contact the cathode material and improve the transmission of lithium ions.

[0110] In order to improve the problem of impedance increase caused by coating of the solid electrolyte on the surface of the cathode material, the thickness of the solid electrolyte ranges from greater than 0 to less than or equal to 3 μm, preferably, greater than 0 to less than or equal to 100 nm.

[0111] In the above-mentioned greater than 0 and less than or equal to 3μm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1nm, 1nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1500nm, 1800nm, 2000nm, 2100nm, 2500nm, 2990nm, 3000nm, etc., and the range value between any two of the above-mentioned point values.

[0112] In one embodiment, the solid electrolyte includes at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0113] Polymer solid electrolytes are usually composed of a complex of high molecular weight polymers and metal salts.

[0114] Oxide solid electrolytes, including lithium lanthanum zirconium oxide (Li7La3Zr2O 12 ), lithium lanthanum titanium oxide, etc. Structurally, the oxide solid electrolyte structure includes oxygen.

[0115] Sulfide solid electrolytes, including Li2S-P2S5, structurally speaking, include sulfur in the structure of sulfide solid electrolytes.

[0116] The present application does not limit the type of solid electrolyte, including but not limited to at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0117] In one embodiment, the polymer solid electrolyte includes at least one of polyethylene oxide, polymethacrylate, and polyvinylidene fluoride; and / or the oxide solid electrolyte includes Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4、Li7La3Zr2O 12 , at least one of LiPON (Li2PO2O); and / or, sulfide solid electrolyte Li2S-P2S5, Li2S-P2S5-MS x At least one of, M includes at least one of Si, Sn, Al, Se, and Ge.

[0118] The polymer solid electrolyte includes but is not limited to at least one of polyethylene oxide, polymethacrylate, and polyvinylidene fluoride. The oxide solid electrolyte includes but is not limited to Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4、Li7La3Zr2O 12 , LiPON (Li2PO2O). Sulfide solid electrolytes include but are not limited to Li2S-P2S5, Li2S-P2S5-MS x At least one of, M includes at least one of Si, Sn, Al, Se, and Ge.

[0119] The present application also provides a cathode electrode plate, which includes a current collector and a coating disposed on at least one side of the current collector, wherein the coating includes a cathode composite material such as.

[0120] like Figure 2 and Figure 3 As shown, the cathode electrode 100 includes a current collector 10 and a coating disposed on one side of the current collector 10. Figure 2 As shown, the coating can be a layer structure, such as Figure 3 As shown, the coating can be a two-layer structure, and of course the coating can also be arranged on the other side of the current collector.

[0121] The coating includes a cathode composite material, which includes a cathode material and a solid electrolyte coated on the surface of the cathode material. The solid electrolyte is used for ion transmission, improves the direct contact between the cathode material and the electrolyte, improves the problem of intercrystalline cracks / intracrystalline cracks in the cathode material, and is beneficial to reduce side reactions, improve battery cycle performance, and reduce the storage gas production of the battery.

[0122] In one embodiment, the mass percentage of the cathode composite material to the total mass of the coating is in the range of 80% to 98%, preferably, 85% to 95%.

[0123] The mass of the cathode composite material is the mass percentage of the total mass of the coating. For example, if the total mass of the coating is M0 and the mass of the cathode composite material in the coating is m0, the calculation formula is (m0 / M0)×100%.

[0124] In order to improve the performance of the battery, the mass percentage of the cathode composite material to the total mass of the coating layer is in the range of 80% to 98%, preferably, 85% to 95%.

[0125] It can be understood that the coating is a one-layer structure, which may include a cathode composite material. The coating may also be a multi-layer structure, in which at least one layer includes a cathode composite material, and at least another layer may not include a cathode composite material. For example, the coating includes a two-layer structure, the first layer is arranged close to the current collector, and the second layer is arranged on the surface of the first layer. In this case, the first layer may include a cathode composite material, and the second layer may include a cathode material.

[0126] In the above-mentioned 80% to 98%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0127] In one embodiment, the mass percentage of the solid electrolyte in the cathode composite material to the total mass of the coating layer is in a range of 0.4% to 2%.

[0128] In order to improve the performance of the battery, the mass percentage of the solid electrolyte in the cathode composite material to the total mass of the coating is in the range of 0.4% to 2%. It can be understood that as the concentration of the solid electrolyte in the cathode composite material in the coating increases, the probability of the cathode material and the electrolyte having a side reaction decreases, but as the concentration of the solid electrolyte in the cathode composite material in the coating continues to increase, the pole piece impedance increases and the gram capacity decreases.

[0129] In the above 0.4% to 2%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.4%, 0.5%, 0.7%, 0.9%, 1.0%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, etc., as well as the range values ​​between any two of the above point values.

[0130] In one embodiment, the coating includes at least two active layers, at least two active layers are stacked on the same side of the current collector, at least one active layer is arranged on the current collector, and at least another active layer is arranged on the side of the at least one active layer away from the current collector; the mass percentage of the solid electrolyte in at least one active layer is defined as W1, and the mass percentage of the solid electrolyte in at least another active layer is defined as W2, satisfying W1>W2.

[0131] The coating includes at least two active layers, which means that the coating can be a two-layer structure, or a three-layer, four-layer structure, etc.

[0132] At least two active layers are stacked on the same side of the current collector, for example Figure 3 As shown, the two active layers are located on the same side of the current collector and are stacked on one side of the current collector.

[0133] The mass percentage of the solid electrolyte in an active layer. For example, the mass of an active layer is M1, and the mass of the solid electrolyte in the layer is m1. The mass percentage of the solid electrolyte in the active layer is calculated as (m1 / M1)×100%.

[0134] One active layer is arranged on the current collector, and the other active layer is arranged on the side of at least one active layer away from the current collector. Thus, according to the distance from the current collector, one active layer is close to the current collector, and the other active layer is arranged away from the current collector. The mass percentage W1 of the solid electrolyte in the active layer close to the current collector is greater than the mass percentage W2 of the solid electrolyte in the active layer away from the current collector. In this way, the contact between the electrolyte and the cathode material in the active layer close to the current collector is reduced, the infiltration of the electrolyte into the active layer away from the current collector is improved, the ion transmission performance is improved, and the battery performance is improved.

[0135] It is understandable that, in theory, the transport of ions mainly depends on the electrolyte. Although solid electrolytes have the function of transporting ions, the effect is not as good as that of electrolytes. In order to balance the contact between the electrolyte and the cathode material, solid electrolytes of different concentrations are distributed in different active layers. Specifically, the concentration of the solid electrolyte distributed from close to the current collector to away from the current collector shows a decreasing trend, which improves the side reaction of the cathode material in the active layer close to the current collector, while also maintaining the wetting of the active layer away from the current collector with the electrolyte. While reducing the side reactions caused by the contact between the electrolyte and the cathode material, it also improves the ion transport performance.

[0136] In one embodiment, 0.4%≤W1≤4%, preferably, 0.4%≤W1≤3%; and / or, 0≤W2≤3.5%, preferably, 0≤W2≤2.5%.

[0137] In order to improve the contact between the electrolyte and the cathode material, and to improve the ion transport performance, the mass percentage W1 of the solid electrolyte in the active layer close to the current collector satisfies 0.4%≤W1≤4%, preferably 0.4%≤W1≤3%; the mass percentage W2 of the solid electrolyte in the active layer far from the current collector satisfies 0≤W2≤3.5%, preferably 0≤W2≤2.5%.

[0138] In the above 0.4%≤W1≤4%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.4%, 0.5%, 0.7%, 0.9%, 1.0%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, 2.5%, 2.7%, 3%, 3.5%, 4%, etc., and the range values ​​between any two of the above point values.

[0139] In one embodiment, the compacted density of the coating is in the range of 2.0 g / cm 3 Up to 5.0g / cm 3 , preferably, 2.3 g / cm 3 Up to 4.5g / cm 3 .

[0140] Compacted density, compacted density = surface density / (thickness of the pole piece after rolling - thickness of the current collector), unit: g / cm 3 Areal density is the mass per unit area of ​​a material of a specified thickness.

[0141] In order to improve the wetting of the electrolyte to the coating and improve the transmission of ions, the compaction density of the coating is in the range of 2.0g / cm 3 Up to 5.0g / cm 3 , preferably, 2.3 g / cm 3 Up to 4.5g / cm 3 .

[0142] Above 2.0g / cm 3 Up to 5.0g / cm 3 In the range, the values ​​include the minimum and maximum values ​​of the range, and each value between the minimum and maximum values, and specific examples include but are not limited to the point values ​​in the embodiment and 2.0 g / cm 3 , 2.3g / cm 3 , 2.5g / cm 3 , 2.7g / cm3 、3.0g / cm 3 , 3.5g / cm 3 , 4.0g / cm 3 , 4.5g / cm 3 , 5.0g / cm 3 Etc., and the range value between any two of the above point values.

[0143] In one embodiment, the coating includes at least two active layers, at least two active layers are stacked on the same side of the current collector, at least one active layer is arranged on the current collector, and at least another active layer is arranged on the side of the at least one active layer away from the current collector; the compaction density of at least one active layer is defined as ρ1, and the compaction density of at least another active layer is defined as ρ2, satisfying ρ1>ρ2.

[0144] The compaction density of the coating will increase with the increase of solid electrolyte. As the compaction density increases, the voids in the coating will decrease. In order to balance the side reactions caused by the contact between the cathode material and the electrolyte and to improve the transport of ions, the coating includes at least two active layers, at least one active layer is arranged on the current collector, and at least another active layer is arranged on the side of the at least one active layer away from the current collector. Then, one active layer is arranged close to the current collector, and the other active layer is arranged away from the current collector compared to the first active layer. The concentration of the solid electrolyte in the active layer close to the current collector is higher than the concentration of the solid electrolyte in the active layer away from the current collector. In this way, the compaction density ρ1 of the active layer close to the current collector is greater than the compaction density ρ2 of the active layer away from the current collector. In this way, the side reactions between the cathode material and the electrolyte in the active layer close to the current collector are improved, the infiltration of the active layer away from the current collector with the electrolyte is improved, and the transport of ions is improved.

[0145] The present application also provides a method for preparing a cathode composite material, comprising: preparing a cathode material and a solid electrolyte, and mixing the cathode material and the solid electrolyte to obtain the cathode composite material.

[0146] The solid electrolyte is arranged on the surface of the cathode material by simple physical mixing to obtain a cathode composite material. The preparation method is simple, low-cost and convenient for large-scale production.

[0147] In one embodiment, the step of mixing the cathode material and the solid electrolyte includes: stirring and mixing the cathode material and the solid electrolyte at a stirring rate of 800 rpm to 2000 rpm and a stirring time of 2 h to 8 h to obtain a cathode composite material.

[0148] In order to mix effectively, the cathode material and the solid electrolyte are stirred and mixed at a stirring rate of 800 rpm to 2000 rpm and a stirring time of 2 h to 8 h to obtain a cathode composite material.

[0149] like Figure 1 As shown, the present application also provides a method for preparing a cathode electrode sheet, comprising: mixing a cathode material with a solid electrolyte to obtain a cathode composite material; mixing the cathode composite material, a binder, a conductive agent and a solvent to obtain a slurry; coating the slurry on a current collector, drying and cold pressing to obtain a cathode electrode sheet.

[0150] The cathode material is mixed with a solid electrolyte to obtain a cathode composite material, the cathode composite material, a binder, a conductive agent and a solvent are mixed to obtain a slurry, and the slurry is coated on a current collector, dried and cold pressed to obtain a cathode electrode sheet. This step is simple and convenient for large-scale production.

[0151] In one embodiment, the step of coating the slurry on the current collector, drying, and cold pressing to obtain the cathode electrode sheet includes: preparing slurry for at least two active layers, coating the slurry of one active layer on the current collector, and drying; coating the slurry of another active layer on an active layer, drying, and cold pressing to obtain the cathode electrode sheet; the mass percentage of the solid electrolyte in the slurry of one active layer is greater than the mass percentage of the solid electrolyte in the slurry of the other active layer.

[0152] In order to prepare a multi-layer coating, the step of coating the slurry on the current collector, drying, and cold pressing to obtain a cathode electrode sheet includes: preparing slurry of at least two active layers, coating the slurry of one active layer on the current collector, and drying; coating the slurry of another active layer on the first active layer, drying, and cold pressing to obtain a cathode electrode sheet; the mass percentage of the solid electrolyte in the slurry of one active layer is greater than the mass percentage of the solid electrolyte in the slurry of another active layer. In this way, the side reaction between the cathode material and the electrolyte in one active layer is improved, the transmission of ions in another active layer is improved, and the battery performance is improved.

[0153] The present application provides a battery, comprising: an anode electrode piece, a cathode electrode piece, a separator and an electrolyte, wherein the cathode electrode piece is the cathode electrode piece as described above or the cathode electrode piece obtained by the preparation method of the cathode electrode piece as described above. Since the cathode electrode piece adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0154] The present application also provides an electrical device, which includes the above-mentioned battery. Since the battery adopts all the technical solutions of all the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0155] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0156] In one embodiment of the present application, a secondary battery is provided.

[0157] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.

[0158] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0159] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0160] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0161] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0162] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0163] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0164] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0165] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0166] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0167] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0168] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0169] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0170] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0171] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0172] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0173] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0174] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0175] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0176] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0177] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0178] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0179] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0180] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0181] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0182] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0183] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.

[0184] In some embodiments, reference Figure 5 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0185] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0186] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0187] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0188] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0189] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0190] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0191] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0192] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0193] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0194] Example

[0195] Anode plate preparation

[0196] Artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) were added into deionized water in a mass ratio of 96.2:1.0:1.6:1.2, and stirred and mixed thoroughly to prepare negative electrode slurry (solid content 63%). 2 The loading amount is coated on the negative electrode collector copper foil, and then dried, cold pressed and cut to obtain the negative electrode sheet.

[0197] Electrolyte

[0198] At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 is dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 is 1 mol / L.

[0199] Diaphragm

[0200] A commercially available PE microporous film with a thickness of 7 μm and an average pore size of 80 nm (from Zhuogao Electronic Technology Co., Ltd.) was used.

[0201] Battery Assembly

[0202] The cathode electrode sheet, separator and anode electrode sheet are stacked and wound in order, and cold-pressed (during which the separator and the electrode sheet are bonded) to obtain a battery cell; the battery cell is placed in an outer package, and the prepared electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery is obtained.

[0203] Performance Testing

[0204] Battery Gas Generation Test

[0205] The battery cell was adjusted to 95% SOC, the voltage was monitored every day for recharging, and it was stored at 60°C for 60 days. The gas production was measured by the water drainage method.

[0206] Impedance test

[0207] Take the cathode electrode to prepare a symmetrical battery (positive electrode to positive electrode). After adding the electrolyte, test the electrochemical impedance spectrum. The measurement is performed at the open circuit voltage of the battery; the AC amplitude is 5mV; the scanning frequency range is 100kHz~25mHz, and the SIM software that comes with the IM6 electrochemical tester is used to fit and analyze the measured impedance spectrum.

[0208] Example 1

[0209] The solid electrolyte (Li 3.3 La 0.56 TiO3) and cathode materials (NCM811, LiNi 0.8 Co 0.1 Mn 0.1 O2) in a mass ratio of 1:97 to obtain a cathode composite material.

[0210] The cathode composite material, a binder (polyvinylidene fluoride (PVDF)), a conductive agent (carbon black), and a solvent (N-methylpyrrolidone (NMP)) were mixed in a mass ratio of 98:1:1:60 to obtain a slurry.

[0211] The slurry is coated on the current collector aluminum foil, and then dried, cold pressed and cut to obtain the cathode electrode sheet.

[0212] Example 2 and Example 3

[0213] On the basis of Example 1, the mass ratios of the solid electrolyte to the cathode material were adjusted to 1:200 and 1:50 to obtain Examples 2 and 3.

[0214] Example 4

[0215] On the basis of Example 3, the type of solid electrolyte is changed to obtain Example 4.

[0216] Example 5

[0217] On the basis of Example 3, the coating is provided with two layers, and the mass ratio of the solid electrolyte to the cathode material in the first layer is greater than the mass ratio of the solid electrolyte to the cathode material in the second layer.

[0218] Example 6 to Example 12

[0219] On the basis of Example 1, the volume average particle size Dv50 of the solid electrolyte and the cathode material was adjusted to obtain Examples 6 to 12.

[0220] Comparative Example 1: Based on Example 1, no solid electrolyte is added to obtain Comparative Example 1.

[0221] Table 1 Experimental parameters list

[0222]

[0223]

[0224] Table 2 Experimental parameters list

[0225]

[0226]

[0227] Table 3 Performance parameter list

[0228]

[0229] It can be seen from the above table that coating the surface of the cathode material with a solid electrolyte can improve the gas production of the battery and improve the gas production quality assurance of the battery cell. Moreover, it can be seen from Examples 3 and 5 that in the two-layer coating, the mass ratio of the solid electrolyte to the cathode material in the first layer is greater than the mass ratio of the solid electrolyte to the cathode material in the second layer, and the performance is better at this time.

[0230] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. All equivalent structural changes made using the contents of the present application specification and drawings under the inventive concept of the present application, or direct / indirect applications in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A cathode composite material, characterized in that: The cathode composite material comprises a cathode material and a solid electrolyte coated on the surface of the cathode material.

2. The cathode composite material according to claim 1, characterized in that The ratio of the volume average particle size Dv50 of the solid electrolyte to the volume average particle size Dv50 of the cathode material is 1:400 to 1:10, preferably, 1:300 to 1:

50.

3. The cathode composite material according to claim 1 or 2, characterized in that: The volume average particle size Dv50 of the solid electrolyte ranges from 1 nm to 1000 nm, preferably from 10 nm to 500 nm; And / or, the volume average particle size Dv50 of the cathode material is in the range of 100 nm to 20000 nm, preferably, 500 nm to 5000 nm.

4. The cathode composite material according to any one of claims 1 to 3, characterized in that The solid electrolyte is arranged at intervals on the surface of the cathode material; And / or, the thickness of the solid electrolyte is in the range of greater than 0 and less than or equal to 3 μm, preferably, greater than 0 and less than or equal to 100 nm.

5. The cathode composite material according to any one of claims 1 to 4, characterized in that The ratio of the mass of the solid electrolyte to the mass of the cathode material is 1:200 to 1:50, preferably, 1:150 to 1:

60.

6. The cathode composite material according to any one of claims 1 to 5, characterized in that The solid electrolyte includes at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

7. The cathode composite material according to claim 6, characterized in that The polymer solid electrolyte includes at least one of polyethylene oxide, polymethacrylate, and polyvinylidene fluoride; And / or, the oxide solid electrolyte includes Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4、Li7La3Zr2O 12 , at least one of LiPON; And / or, the sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-MS x At least one of, M includes at least one of Si, Sn, Al, Se, and Ge.

8. A cathode electrode, characterized in that: The cathode electrode sheet comprises a current collector (10) and a coating disposed on at least one side of the current collector (10), wherein the coating comprises the cathode composite material according to any one of claims 1 to 7.

9. The cathode electrode according to claim 8, characterized in that: The mass percentage of the cathode composite material to the total mass of the coating layer is in the range of 80% to 98%, preferably, 85% to 95%.

10. The cathode electrode according to claim 8 or 9, characterized in that: The mass percentage of the solid electrolyte in the cathode composite material to the total mass of the coating layer is in the range of 0.4% to 2%.

11. The cathode electrode according to any one of claims 8 to 10, characterized in that: The coating layer comprises at least two active layers, the at least two active layers are stacked and arranged on the same side of the current collector, at least one of the active layers is arranged on the current collector, and at least another of the active layers is arranged on a side of at least one of the active layers away from the current collector; The mass percentage of the solid electrolyte in at least one of the active layers is defined as W1, and the mass percentage of the solid electrolyte in at least another active layer is defined as W2, satisfying W1>W2.

12. The cathode electrode according to claim 11, characterized in that: 0.4%≤W1≤4%, preferably, 0.4%≤W1≤3%; And / or, 0≤W2≤3.5%, preferably 0≤W2≤2.5%.

13. The cathode electrode according to any one of claims 8 to 12, characterized in that: The compacted density of the coating is in the range of 2.0 g / cm 3 Up to 5.0g / cm 3 , preferably, 2.3 g / cm 3 Up to 4.5g / cm 3 .

14. The cathode electrode according to claim 13, characterized in that: The coating layer comprises at least two active layers, the at least two active layers are stacked and arranged on the same side of the current collector, at least one of the active layers is arranged on the current collector, and at least another of the active layers is arranged on a side of at least one of the active layers away from the current collector; The compaction density of at least one of the active layers is defined as ρ1, and the compaction density of at least another active layer is defined as ρ2, satisfying ρ1>ρ2.

15. A method for preparing a cathode composite material according to any one of claims 1 to 7, characterized in that: include: A cathode material and a solid electrolyte are prepared, and the cathode material and the solid electrolyte are mixed to obtain a cathode composite material.

16. The method for preparing the cathode composite material according to claim 15, characterized in that: The step of mixing the cathode material and the solid electrolyte comprises: The cathode material and the solid electrolyte are stirred and mixed at a stirring rate of 800 rpm to 2000 rpm and a stirring time of 2 h to 8 h to obtain a cathode composite material.

17. A method for preparing a cathode electrode sheet according to any one of claims 8 to 14, characterized in that: include: mixing the cathode material with the solid electrolyte to obtain a cathode composite material; Mixing the cathode composite material, a binder, a conductive agent and a solvent to obtain a slurry; The slurry is coated on a current collector, dried, and cold-pressed to obtain a cathode electrode sheet.

18. The method for preparing a cathode electrode sheet according to claim 17, characterized in that: The step of coating the slurry on the current collector, drying, and cold pressing to obtain the cathode electrode sheet includes: Prepare at least two layers of active layer slurry, apply one of the active layer slurry on the current collector, and dry; The slurry of the other active layer is coated on the one active layer, dried, and cold pressed to obtain a cathode electrode sheet; The mass percentage of the solid electrolyte in the slurry of one active layer is greater than the mass percentage of the solid electrolyte in the slurry of another active layer.

19. A battery, characterized in that: include: An anode electrode sheet, a cathode electrode sheet, a separator and an electrolyte, wherein the cathode electrode sheet is the cathode electrode sheet as described in any one of claims 8 to 14 or the cathode electrode sheet obtained by the preparation method of the cathode electrode sheet as described in claim 17 or 18.

20. An electrical equipment, characterized in that: The electrical device comprises the battery according to claim 19.

Citation Information

Patent Citations

  • Battery positive electrode and preparation method thereof, and lithium ion secondary battery

    CN103633289A

  • Positive electrode material and preparation method thereof, positive electrode plate and preparation method and application thereof

    CN116093276A

  • Manufacturing method of composite cathode active material, manufacturing method of all-solid battery, and composite cathode active material

    JP2011238523A

  • KR20230026263A

Cited By

  • Battery positive electrode material, positive electrode plate, and preparation method and application of battery positive electrode material and positive electrode plate

    CN121076110A